Crafting meaningful motifs and products : Arts-based activities to inspire ideation - Rönkkö, Marja-Leena; Aerila, Juli-Anna (OsloMet - Oslo Metropolitan University, 2026)
This article reports the implementation of a crafting process aiming to enhance personal significance during the ideation phase of a nature-themed fabric motif. The ideation phase of the motif was implemented in a garden setting, and it consisted of several arts-based activities such as Dance'n'Paint, River of Experience, and creative writing. In this study, the crafting process of one participant was investigated via semiotic phenomenological analysis, leveraging the diverse materials provided by the participant. This analysis aimed to ponder how the crafting process with arts-based activities progressed from ideation to fabric motif and product creation. The findings revealed that arts-based activities significantly influenced the participant's creative process by giving the participant materials, motivation and meaningfulness for the fabric motif designing. In the study, the crafting process became meaningful for the participant as a positive experience of participation in an arts-based workshop, as a learning experience in motif designing and as a personal experience of memory work. These experiences became deeply embedded in the fabric motif and the ready-made tunic. The arts-based activities chosen for this study might apply to different contexts and themes. However, the nature theme chosen for this study might also be relevant from the sustainability perspective.